Odpowiedzi

2009-12-17T10:31:34+01:00
A) 10 m/s= 10× (0,001km/(1/3600)h)= 10× (0,001km×3600h)= (0,01×3600) km/h = 36km/h
b) 16 m/s = 16× (0,001km/(1/3600)h)= 16* (0,001km×3600h)= (0,016×3600) km/h= 57,6 km/h
c)50 cm/s= 50× (0,00001km/(1/3600)h)= 16× (0,00001km×3600h)= (0,0005×3600) km/h= 1,8 km/h
d) 13 mm/s= 13× (0,000001km/(1/3600)h)= 13× (0,000001km×3600h)= (0,000013×3600) km/h= 0,0468 km/h
23 3 23
2009-12-17T10:34:00+01:00
Wzór podstawowy:
1 m/s = 1 m/s * 3600 s/h = 3600 m/h = 3,6 km/h

a). 10 m/s = 10 m/s * 3600 s/h = 36000 m/h = 36 km/h

b). 16 m/s = 16 m/s * 3600 s/h = 57600 m/h = 57,6 km/h

c). 50 cm = 0,5 m
0,5 m/s = 0,5 m/s * 3600 s/h = 1800 m/h = 1,8 km/h

d). 13 mm = 0,013 m
0,013 m/s = 0,013 m/s * 3600 s/h = 46,8 m/h = 0,0468 km/h
40 4 40